Impact of Hot Water and Modified Atmosphere Packaging Treatments on the Postharvest Quality of Pomegranate Fruit (Punica granatum cv. ‘Hicaznar’) - Ahmet Erhan Özdemir; Elif Çandır (Journal of Agricultural Sciences)
Hot water (HW) and modified atmosphere packaging (MAP) treatments were evaluated to maintain postharvest quality of pomegranate fruit (Punica granatum cv. ‘Hicaznar’). Pomegranates were subjected to hot water (HW) treatment (at 50 °C for 3 min) and packaged with or without MAP bags. Fruit was then kept at 6 °C for 6 months and at 20 °C for 7 days after cold storage period. The untreated and unpackaged fruit was served as a control treatment (C). MAP and HW+MAP treatments was more effective in reducing weight loss, fungal decay and husk scald, compared to HW and C treatments. The lightness and red color intensity of husk and aril (higher values of L* and C* and lower values of h°) were maintained better in the packaged fruit with MAP (MAP + HW+MAP treatments). The unpackaged fruit from HW and C treatments became unmarketable while those from MAP and HW+MAP treatments were still marketable after 6 months of cold storage and shelf life period. Although fungal decay incidence was low in HW-treated fruit, relatively high scald incidence and weight loss had adverse effect on overall visual acceptability of HW-treated fruit. Hot water dipped pomegranate fruit cv. ‘Hicaznar’ (50 °C for 3 min) could be kept in MAP bags for 6 months at 6 °C and for 7 days 20 °C without adverse effect on quality.